Toxicokinetics and Tissue Distribution of the Hepatotoxic Triterpenoid Saponin Pterocephin A in Rats Using the Ultra-Performance Liquid Chromatography–Tandem Mass Spectrometry (UPLC-MS/MS) Method - Yiran Xiong; Zhaoyue Dong; Hongxu Zhou; Jingxin Mao; Lingjiang Zeng; Yunbin Jiang; Fancheng Meng; Zhihua Liao; Min Chen (Molecules, 2024)
Pterocephin A is a natural triterpenoid saponin isolated from Pterocephalus hookeri, a traditional Tibetan medicine with slight toxicity, which can induce liver injury in rats. This study aimed to establish a sensitive and reliable UPLC-MS/MS method for exploring the toxicokinetics and tissue distribution of pterocephin A following single intravenous and intragastric administration. Pterocephin A and prosapogenin 1C (internal standard, IS) were extracted using a simple protein precipitation technique with methanol as the precipitant for plasma samples and methanol/acetonitrile = 1:1 (v/v) for tissue samples. UPLC separation was achieved by gradient elution with 0.3 mL/min and a mobile phase consisting of 5 mM ammonium formate (A) and acetonitrile (B) (0–2 min 30% B; 2–4 min: 30–80% B; 4–5 min: 80–98% B; 5–6.5 min: 98% B; 6.5–7 min: 98–30% B; and 7–8 min: 30% B, v/v) with a column temperature of 35 °C. MS spectrometry adopted negative ion scanning mode, primary MS spectrometry adopted full scan monitoring mode, and secondary MS spectrometry adopted targeted MS2 scan monitoring mode. The assay exhibited a linear dynamic range of 0.02–15 μg/mL for pterocephin A in biological samples, with the low limit of quantification set at 0.02 μg/mL. Non-compartmental toxicokinetic parameters indicated that pterocephin A was well absorbed into the systemic circulation and had a long residual time after intravenous (10 mg/kg) and intragastric (60 mg/kg) administration, as it could still be detected after 72 h. Tissue distribution analysis revealed detectable levels of pterocephin A in various tissues, and a high concentration was maintained in the liver after intravenous (10 mg/kg) administration, with the highest concentration being 610.95 ± 25.73 ng/mL and a specific distribution pattern of liver > lung > kidney > intestine > spleen > testes > heart > stomach. The toxicokinetic process and tissue distribution characteristics of pterocephin A were expounded in this study, which can provide relevant data support for further research and clinical application of pterocephin A with its slight toxicity.